2017
DOI: 10.1021/acsinfecdis.7b00157
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Phenothiazines: Optimization, Characterization of Mechanism, and Modulation of Neuroreceptor Activity

Abstract: New classes of antifungal drugs are an urgent unmet clinical need. One approach to the challenge of developing new antifungal drugs is to optimize the antifungal properties of currently used drugs with favorable pharmacologic properties, so-called drug or scaffold repurposing. New therapies for cryptococcal meningitis are particularly important given its worldwide burden of disease and limited therapeutic options. We report the first systematic structure-activity study of the anticryptococcal properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…The majority of these cases are seen in patients with HIV/AIDS. Furthermore, mortality associated with CM shows a health disparity with a mortality rate of only 20% in developed countries and 40% in middle-income countries but 70% in low-income countries in sub-Saharan Africa. …”
mentioning
confidence: 99%
“…The majority of these cases are seen in patients with HIV/AIDS. Furthermore, mortality associated with CM shows a health disparity with a mortality rate of only 20% in developed countries and 40% in middle-income countries but 70% in low-income countries in sub-Saharan Africa. …”
mentioning
confidence: 99%
“…It was further demonstrated that the hybrid 62 led to an additive inhibition with fluconazole (2-fold reduction) against C. albicans with mutations in its efflux pump, which makes the strain more resistant to fluconazole. Antagonism of calmodulin by the phenothiazine scaffold correlates well with its antifungal activity [ 84 ].…”
Section: Antimicrobial Hybridsmentioning
confidence: 99%
“…Notably, the architectures of the TFP-binding pockets, the number of bound TFP molecules, and the orientation of the TFP molecules are quite different between S100A4, troponin C, and calmodulin (Cook et al 1994;Feldkamp et al 2015;Malashkevich et al 2010;Vandonselaar et al 1994;Vertessy et al 1998). Given the differences in TFP-binding modes and the large number of phenothiazine derivatives that are available, it may be possible to selectively target these proteins with appropriate phenothiazine analogs (Brem et al 2017;Montoya et al 2018;Pluta et al 2017).…”
Section: Small Molecule Inhibition Of S100 Proteinsmentioning
confidence: 99%